Pembelajaran Kolaboratif Mahasiswa dan Siswa: Aksi Nyata Profil Pelajar Pancasila di SMPN 3 Pematangsiantar - Richard David Siburian; Trinita Oktheresia Ompusunggu; Ivana Melina Pasaribu; Romianti Suryanita Siregar; Dearma Amelia Sirait; Dwi Angeli Pardede; Jessica Valentina Sitompul; Fadlan Hanafi Siregar; Tumpal Manahara Siahaan (Young Journal of Social Sciences and Humanities, 2025)
Value transformation in education is often hindered by the dominance of instrumental-cognitive learning that lacks reflective experience. This condition creates a gap between conceptual understanding and the internalization of national values embodied in the Profil Pelajar Pancasila (Pancasila Student Profile). This study aims to analyze the practice of cognitive collaboration between university students and junior high school students in implementing the Pancasila Student Profile at SMPN 3 Pematangsiantar. A qualitative approach was employed with data collected through observation, interviews, and documentation. Data were analyzed through the stages of reduction, presentation, and conclusion drawing using a narrative approach. The findings reveal that cognitive collaboration not only strengthens reasoning and problem-solving skills but also fosters moral awareness, learning autonomy, and a spirit of cooperation among students. University students acted as facilitators who cultivated reflective and participatory learning spaces where Pancasila values were internalized through lived experiences. This study concludes that the Pancasila Student Profile is not merely a normative framework but a transformative and humanistic educational praxis that shapes independent, reflective, and morally grounded learners.